Analisis Uji Inderawi, Uji Kesukaan, Mutu Fisik, dan Kimiawi pada Pengembangan Snack Inovatif Berbasis Jagung (Zea mays L.) “Corn Lava Jasu Pearls” dengan Formulasi Vla Berbeda - Dinda Putria Zahira; Octavianti Paramita (Jurnal Ragam Pengabdian, 2026)
This study aimed to evaluate the effect of different formulations on the sensory characteristics, consumer acceptance, physical properties, and chemical composition of Corn Lava Jasu Pearls. An experimental method was applied using two formulations, namely F0 and F1. Sensory evaluation was conducted by trained panelists (three experts) to assess aroma, taste, and texture attributes, while the hedonic test was performed by untrained panelists (80 participants) to evaluate product acceptability. Physical analysis focused on color characteristics, and chemical analysis included nutritional composition assessment. Sensory data from trained panelists were analyzed using one-way ANOVA, whereas hedonic data were analyzed using the Mann–Whitney test.The results showed that formulation differences did not significantly affect sensory attributes evaluated by trained panelists (p > 0.05). However, the hedonic test indicated significant differences in consumer preference between formulations. In addition, formulation variations influenced color characteristics and chemical composition, with formulation F1 showing advantages in terms of nutritional value. development of Corn Lava Jasu Pearls should consider a balance between nutritional enhancement and consumer acceptance.